DARK SIDE OF THE PLEA BARGAINING - Bajović, Vanja (Zbornik radova Pravnog fakulteta u Novom Sadu, 2019)
Plea bargaining is a procedural mechanism through which criminal case is resolved without trial, by consensus of the parties. The agreement consists of the defendant pleading guilty in exchange for prosecutor’s promise to charge him less serious than is supported by the evidence, not to charge him for some crimes or to request certain sentence. Plea bargaining is product and significant part of the American criminal justice, where the vast majority of criminal cases are settled on that way. This institute was introduced in Serbian law in 2009, with the aim to simplify criminal procedure, making it more efficient and faster. In the Article is discussed the extent of plea bargaining’s innocence problem.  The basic question is whether is true the statement of Professor Alshuler that a plea bargaining is ‘’a nearly perfect system for convicting the innocent’’. In regard with that, the questions that are discussed are why innocent plead guilty, whether policy of ‘zero tolerance’ on criminality favour plea agreements, haw the prosecutor becomes the most importunate figure of the criminal justice system etc. According to Serbian CPC defense is not allowed to cross-examine co-defendant who is already convicted or prosecuted in severed criminal proceedings, but instead of that judge just read the transcript of his testimony (Art. 406 ). The Highest Court of Cassation even more broadened the effects of this problematic provision, allowing as evidence against defendant the statement of co-defendant given in the plea agreement, instead of his direct examination! In the last part of the paper is analysed this problematic view and the extended effect of plea agreement in Serbian case law. Key words: plea agreement, guilty plea, innocence